Effects of climatic conditions on sex ratios in nests of broad snouted caiman - Simoncini, Melina Soledad (2014)
Caiman latirostris has temperature-dependent sex determination and is potentially susceptible to environmental temperature fluctuations and, thus, to the global climate change phenomena. Considering the potential consequences of increasing temperatures for Ca. latirostris offspring, we examined the effects of climatic conditions on sex ratios produced by caimans in wild nests and in particular how climate variables affect nest temperature and the percentage of females produced. We also explored the potential consequences of a hypothetic 0.5 and 1.0°C increase in nest temperature on caiman populations. The proportion of females produced from nests in the wild varied among reproductive seasons, as mean nest temperatures varied between 27.1 and 33.9°C. However, after seven seasons the sex ratio biased toward females, and only during extreme events (strong El Niño Southern Oscillation event, La Niña) was there a reduction in the percentage of females produced in the wild. In the hypothetic scenarios of global warming, we predict a decrease of unisexual female nests, with nests containing both sexes or unisexual male nests becoming more frequent. Entire clutches might be lost if nest temperatures rise above 34.5°C for extended periods. However, it is possible that females modify their nesting timing and behavior to select thermally suitable nest environments.